JPEG 2000 Syntax-Compliant Encryption Preserving Full Scalability - Zhu, Bin Benjamin; Yang, Yang; Li, Shipeng (IEEE Int. Conf. Image Processing 2005, 2005)
An efficient syntax-compliant encryption scheme for JPEG 2000 and motion JPEG 2000 is proposed in this paper. Compressed visual data is completely encrypted yet the full scalability of the unencrypted codestream is completely preserved to allow near RD-optimal truncations and other manipulations securely without decryption. Compared with other reported schemes, our scheme shows advantages on syntax compliance, compression overhead, scalable granularity, and error resilience. In addition to preserving the original scalability, a JPEG 2000 codestream encrypted with our scheme has the same error resilience capability as the unencrypted codestream. The encrypted codestream is still syntax-compliant so that an encryption-unaware decoder can still decode the encrypted codestream, although the decoded visual data is completely garbled and meaningless. Our scheme has virtually no adverse impact on the compression efficiency.